Para o estudo da fiscalidade régia em Portugal: as inquirições gerais dos séculos XIII e XIV - Sottomayor-Pizarro, José Augusto de (2019)
From the analysis of the texts of the General Inquiries promoted by the Portuguese monarchs, between the beginning of the thirteenth century and the middle of the fourteenth century, we seek to understand how the royal power gradually became imposed on the manorial powers, while At the same time, it has created an increasingly accurate perception of the size and scope of its capacity for economic and political oversight.